Sistem Pengenalan Wajah pada Keamanan Ruangan Berbasis Convolutional Neural Network - Sunardi, S; Fadlil, Abdul; Prayogi, Denis (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Face recognition is a biometric system that is widely applied in various fields especially in the security for identify and verify purposes. For every method of face recognition, they have a unique ways on the process with their advantages and disadvantages themselves. This study designs a face recognition system that is applied to a room security system using the Convolutional Neural Network (CNN). This method works by imitating the way nerve cells to communicate with interrelated neurons or rather mimics how artificial neural networks work in humans. The process of taking images as training data and the face recognition process using a webcam camera installed on a Raspberry pi-based device and python programming language with tensorflow library. Based on the results of research obtained using 875 data samples which were divided into 75% for training and 25% (or 219 data) for testing data produce predictions with 100% accuracy that means all data were successfully recognized.